LEARNING ENGLISH UTILISING ONLINE PLATFORMS DURING COVID -19 IN TERTIARY LEVEL: INDONESIAN EFL LEARNERS' RETROSPECTIVE PERCEPTION - Rudi Suherman; Sri Yunita; Siti Nurjanah Hadiati (University of Kuningan, 2021)
This study aimed to examine the Indonesian EFL learners' Retrospective Perception toward utilising online platforms in teaching English as a foreign language during a pandemic. The mixed quantitative and qualitative research design method is employed to achieve this goal. Seventy-five EFL learners from three different universities who took English for general communication courses were recruited in this study. The data were obtained by deploying two research instruments: questionnaires and a retrospective interview. Many participants preferred to select the most suitable and economical online platform to maximise their online learning experience. They also regard that learning effectiveness and efficiency can only be achieved by utilising blended synchronous and asynchronous modes. The findings also show that lecturers pose a fundamental role in helping students maximise their learning experiences. Thus, lecturer-student engagement during online learning is inevitably essential.